2023
DOI: 10.2196/41926
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Smartphone-Based Remote Interventions on Dietary Intake, Physical Activity, Weight Control, and Related Health Benefits Among the Older Population With Overweight and Obesity in China: Randomized Controlled Trial

Abstract: Background Traditional health management requires many human and material resources and cannot meet the growing needs. Remote medical technology provides an opportunity for health management; however, the research on it is insufficient. Objective The objective of this study was to assess the effects of remote interventions on weight management. Methods In this randomized controlled study, 750 participants we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
(33 reference statements)
0
4
0
1
Order By: Relevance
“…As for the results, a weight reduction related to the technologies used was observed in the majority of the studies [ 39 , 41 , 43 , 45 , 46 , 49 , 52 , 53 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 64 , 65 , 66 , 67 , 68 ]. Additionally, six studies described a reduction in body fat among participants [ 39 , 41 , 57 , 58 , 64 , 67 ] and in nine papers, a decrease in BMI was also showed beyond weight loss [ 41 , 49 , 52 , 54 , 55 , 56 , 57 , 64 , 66 , 68 ]. Moreover, some authors reported waist or hip circumference reductions in the intervention groups [ 39 , 41 , 46 , 57 , 58 , 64 , 67 ].…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…As for the results, a weight reduction related to the technologies used was observed in the majority of the studies [ 39 , 41 , 43 , 45 , 46 , 49 , 52 , 53 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 64 , 65 , 66 , 67 , 68 ]. Additionally, six studies described a reduction in body fat among participants [ 39 , 41 , 57 , 58 , 64 , 67 ] and in nine papers, a decrease in BMI was also showed beyond weight loss [ 41 , 49 , 52 , 54 , 55 , 56 , 57 , 64 , 66 , 68 ]. Moreover, some authors reported waist or hip circumference reductions in the intervention groups [ 39 , 41 , 46 , 57 , 58 , 64 , 67 ].…”
Section: Resultsmentioning
confidence: 88%
“…After the full-text assessment of the 133 articles that remained, 102 articles were excluded, 42 of them because they did not pertain to our question, 12 because the individuals were affected by other comorbidities, 16 because they were a different type of study from RCT, 7 because they considered a young age population (<18 years), 4 because did not have control groups, and 21 because they did not consider the assessment of changes in PA. Finally, we included 31 articles that met the inclusion criteria ( Figure 1 ) [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dado que el paciente puede tener cierta precaución al dar opinión sobre su profesional de referencia, se hizo énfasis en el anonimato de la respuesta, destacando que una parte significativa de los pacientes pueden considerar su uso como una falta de respeto. Otro aspecto a considerar es que resulta difícil diferenciar el uso del smartphone como app sanitaria o para fin sanitario 15 , 16 (consulta de guía clínica o protocolo) del uso particular, y este hecho puede no ser bien diferenciado por el paciente.…”
Section: Discussionunclassified